2017
DOI: 10.15587/1729-4061.2017.103167
|View full text |Cite
|
Sign up to set email alerts
|

Research into protective properties of electromagnetic screens based on the metal-containing nanostructures

Abstract: Досліджено захисні властивості металополімерних електромагнітних екранів. Встановлено, що підвищен-ня дисперсності металовмісних наночастинок у 2-4 рази знижує коефіцієнт відбиття на 0,15-0,20. Визначено кількісну залежність електрофізичних характеристик розробленого матеріалу від вмісту металевої субстанції. Це дозволило здійснити розрахунки коефіцієнтів екрану-вання і внеску до них захисту за рахунок відбиття елек-тромагнітних хвиль. Мікроструктурними досліджен-нями підтверджено рівномірність розподілу метал… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…In the field of electronics, nanocomposite materials have found wide potential [135]. However, the functioning of electronic devices may hinder other devices, humans, and the environment due to the generation of harmful electromagnetic radiations [136]. Therefore, the applications of nanocomposites have also been extended to shield the harmful electromagnetic interference (EMI) radiations [137,138].…”
Section: Significance Of Electrospun Polymer/nanocarbon Nanocomposite...mentioning
confidence: 99%
“…In the field of electronics, nanocomposite materials have found wide potential [135]. However, the functioning of electronic devices may hinder other devices, humans, and the environment due to the generation of harmful electromagnetic radiations [136]. Therefore, the applications of nanocomposites have also been extended to shield the harmful electromagnetic interference (EMI) radiations [137,138].…”
Section: Significance Of Electrospun Polymer/nanocarbon Nanocomposite...mentioning
confidence: 99%
“…In a thorough survey work [4], it is shown that gradient properties can also be found in materials intended for individual protection and not very suitable for facing surfaces. Research [5] shows that it is possible to obtain a gradient of physical properties in a heterogeneous material.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…As regards the measures and means of protection of welders, it is known that to protect against the harmful effects of MF, they mainly use the shielding of MF sources (welding equipment or welders themselves) [10]. To that end, one can use both well-known metal materials and the latest metal-containing nanostructured shielding materials [11].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%